2019
DOI: 10.1007/s11412-019-09311-4
|View full text |Cite
|
Sign up to set email alerts
|

Are we together or not? The temporal interplay of monitoring, physiological arousal and physiological synchrony during a collaborative exam

Abstract: The coordination of cognitive and non-cognitive interactive processes contributes to successful collaboration in groups, but it is hard to evidence in computer-supported collaborative learning (CSCL). Monitoring is a metacognitive process that can be an indicator of a student's ability to recognize success or failure in collaboration. This study focuses on how monitoring occurs in CSCL during a collaborative exam situation by examining how individual student contributions to monitoring processes are related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 68 publications
4
45
0
2
Order By: Relevance
“…Thus, the amplitude of the peaks was mostly low (mean peak value: 0.19, f = 24,499). This result is in line with earlier studies in authentic learning situations showing low SCR amplitude (Malmberg, Haataja, et al, 2019; Malmberg, Järvelä, et al, 2019; Pijeira‐Díaz et al, 2018). However, even low EDA peak reactivity can signal the need for deliberate monitoring, such as the feeling of knowing (Morris et al, 2008) or errors made during a task (Hajcak et al, 2003), as it reflects a physiological response to external stimuli.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the amplitude of the peaks was mostly low (mean peak value: 0.19, f = 24,499). This result is in line with earlier studies in authentic learning situations showing low SCR amplitude (Malmberg, Haataja, et al, 2019; Malmberg, Järvelä, et al, 2019; Pijeira‐Díaz et al, 2018). However, even low EDA peak reactivity can signal the need for deliberate monitoring, such as the feeling of knowing (Morris et al, 2008) or errors made during a task (Hajcak et al, 2003), as it reflects a physiological response to external stimuli.…”
Section: Discussionsupporting
confidence: 92%
“…Due to the limitations of self‐report data, metacognition and especially monitoring events are often investigated by using observable traces that are viable for capturing monitoring events as they occur in a learning situation. These methods include, for example, think aloud protocols (Azevedo et al, 2011), video observations (Rogat & Linnebrink‐Garcia, 2011), computer logs (Malmberg et al, 2014), eye tracking (Taub et al, 2017) or physiological data (Haataja et al, 2018; Malmberg, Haataja, et al, 2019; Malmberg, Järvelä, et al, 2019). However, due to the implicit nature of metacognitive monitoring, many of the monitoring events remain unseen.…”
Section: The Role Of Metacognitive Monitoring In Self‐regulated Learningmentioning
confidence: 99%
“…The paper also continues the discussion we have started in the journal earlier: How physiological measures can contribute to understanding about productive collaborative learning interactions and how physiological synchrony relates to collaborative learning (e.g. Malmberg et al 2019). Schneiner and colleagues' data come from 42 pairs of participants (N = 84) who worked on programming a robot to solve a variety of mazes.…”
Section: A Forward Look Towards New Experiencesmentioning
confidence: 73%
“…Furthermore, synchronicity is also found in less visible bodily reactions, such as physiological states (i.e., skin arousal measured by electrodermal activity from an individual's wrist). Talking specifically about collaborative situations in small groups, studies have suggested that students tend to synchronize their physiological states during interactions, particularly when monitoring one another's behaviors and cognition (Haataja et al, 2018;Malmberg et al, 2019), and have been able to show initial positive correlations between physiological synchrony and collaboration quality, task performance, and learning gains, by computing the number of cycles between low and high synchronization (Schneider et al, 2020). The aim of these studies was to explore how students monitor behavioral, cognitive, and affective processes during collaboration.…”
Section: What Do We Already Know About the Role Of The Body In The Comentioning
confidence: 99%